Impact of postoperative hepatitis B virus reactivation in hepatocellular carcinoma patients who formerly had naturally suppressed virus. Issue 5 (May 2014) - Lee, Jung Il; Kim, Ja Kyung; Chang, Hye Young; Lee, Jin‐Woo; Kim, Joon Mee; Chung, Hyun Jung; Kim, Young Soo; Lee, Kwan Sik
Abstract Background and Aim Hepatitis B virus (HBV) replication detected before the resection of hepatocellular carcinoma (HCC) is to be controlled by antiviral agents. However, management strategy for patients with preoperatively undetectable HBV DNA without antiviral therapy is not clearly delineated. This study investigated viral reactivation after the liver resection in non‐replicating HBV DNA‐related HCC patients and its impact on the surgical outcome. Methods From 198 patients that underwent liver resection due to HBV‐related HCC, 101 patients who had serially checked serum HBV DNA were analyzed. Results From 101 patients, 33 patients had baseline undetectable HBV DNA. Eleven patients (11/33, 33.3%) had viral replication after the liver resection. The postoperative viral reactivation (HR: 2.144; 95% CI: 1.122–4.097; P = 0.021), along with the existence of satellite nodules (HR: 3.034; 95% CI: 1.1.376–6.689; P = 0.006), existence of microvascular invasion (HR: 2.479; 95% CI: 1.303–4.718; P = 0.006), and HBeAg positivity (HR: 2.059; 95% CI: 1.155–3.670; P = 0.014) predicted recurrence after the surgery. Quantification of intrahepatic total and covalently closed circular DNA (cccDNA) was done in 14 patients whose baseline serum HBV DNA was undetectable without the use of antiviral agent. Amount of intrahepatic cccDNA expressed as copies/hepatocyte in patients with postoperative viral reactivation showed significantly higher than those in patients with sustained negative serum HBV DNA (P = 0.010). Conclusions This study shows that naturally suppressed preoperative HBV without application of antiviral agent does not ensure undetectable serum HBV after the surgery, and postoperative viral reactivation might be associated with HCC recurrence.